The Library Fish - Capucilli, Alyssa Satin, 1957-; Jose, Gladys (New York : Simon & Schuster Books for Young Readers, 2022)
When snow prevents Mr. Hughes from opening the library one day, book-loving Library Fish finds a way to entertain herself and her bookmobile friend,.
"A Paula Wiseman Book."
Ages 4-8.
Grades 2-3.
Keywords: Bookmobiles -- Fiction; Fishes -- Fiction; Libraries -- Fiction; Books and reading -- Fiction